Deviation of the Ummah past and present - Philips, Abu Ameenah Bilal; One Islam Publications (N.S.W, Australia : One Islam Publications, 2004)
The statement of the prophet Muhammad (PBUH) has come true. He foretold on the division of the ummah into various different sects, and tiday it is divided. The reality of this truth dawns upon every muslim who stops to reflects on the situation the muslims are in today. This lecture is a lucid explanation of the causes of this sorry state of affairs and discusses the right way that a muslim should adopt
Title from title screen
Lecturer : Abu Ameenah Bilal Philips
Keywords: Islam -- Customs and practices; Religious life -- Islam